The Role of Education in Empowering the Bhotiya Community: A Socio-Cultural Perspective (International Journal of Scientific Research in Science and Technology, 2024)
The Bhotiya community, mainly living in the Himalayan regions of India, has a distinct cultural and social heritage. The Bhotiya tribe of Uttarakhand is an invention of tradition. If the Himalayas are called the Sartaj of India because of its highest altitude and gigantic form, the Bhotiya community, its original inhabitants, can certainly be called the Sartaj of the primitive caste community of India because of its progressive, entrepreneurial and cultural characteristics. The Bhotias of the central Himalayas are the most developed, prosperous and prosperous of the tribes not only of this region but of the whole of India. Their happiness and prosperity is also an example for non-tribals. This development of this tribe is not the result of any special natural wealth or divine boon. But behind it all, there’s a lot of hard work, dedication and perseverance. He also learned the skill of living happily in adverse climatic and extreme geographical conditions and these difficult circumstances challenged the hidden man in him and inspired him to make his life happy and happy through business. Traditionally semi-nomadic traders, the Bhotiya people have faced significant challenges in accessing formal education due to geographical isolation, socio-economic barriers, and cultural factors. This paper examines the current status of education and literacy rates among the Bhotiya community, explores the barriers they face, the efforts made to improve educational access and the impact of these initiatives on the socio-economic development of the community.